2021
DOI: 10.3390/biology10090906
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Cell-Free DNA Applications. Scoping Review of Clinical Trials

Abstract: We aimed to summarize the current knowledge about the trends in cfDNA application based on the analysis of clinical trials registered until April 2021. International Clinical Trials Registry Platform (ICTRP) and Clinicaltrials.gov were searched with the keywords: “cf-DNA”; “Circulating DNA”; “Deoxyribonucleic Acid”; and “Cell-Free Deoxyribonucleic Acid”. Of 605 clinical trials, we excluded 237 trials, and 368 remaining ones were subject to further analysis. The subject, number of participants, and study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…To sum up, cell-free DNA is a marker with a wide spectrum of applications, successfully applied for many different diseases. Moreover, it is also characterized by a much higher sensitivity than standard biochemical markers [4,127]. To this end, cfDNA tests can be greatly improved by adding a combination with several standard diagnostic biochemical biomarkers to them.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, cell-free DNA is a marker with a wide spectrum of applications, successfully applied for many different diseases. Moreover, it is also characterized by a much higher sensitivity than standard biochemical markers [4,127]. To this end, cfDNA tests can be greatly improved by adding a combination with several standard diagnostic biochemical biomarkers to them.…”
Section: Discussionmentioning
confidence: 99%
“…In organ transplantation, the diagnostic role of cfDNA has been extensively studied in heart, kidney, and lung transplantations [ 96 ]. However, only one study exists on this topic in liver transplantation [ 97 ].…”
Section: Cell-free Dna As a Molecular Marker Or A Diagnostic Toolmentioning
confidence: 99%
“…This could usefully complement the current NGS-based metagenomic approaches to bacterial DNA detection in plasma with significantly improved sensitivity and turnaround time [35,36]. Recent reviews have indicated a growing interest in cfDNA application in cancer and non-cancer studies including sepsis [50], as well as its utility in predicting complicated COVID-19 [51].…”
Section: Stratification Of Bacteraemic Subjectsmentioning
confidence: 99%